A Review On the Application of Nano-Based Materials for Environmental Remediation and Treatment of Infections - Otu, Mercy; Nworie, Felix Sunday (Andalasian International Journal of Applied Science, Engineering and Technology, 2025)
Nanomaterials have emerged as a frontier in applied science, offering innovative solutions in both environmental remediation and biomedical applications. Due to their high surface area, and enhanced reactivity at the nanoscale, nanomaterials exhibit superior antimicrobial efficacy and pollutant interaction capabilities. In healthcare, these materials are incorporated into creams, nail lacquers, ear drops, and dental composites, significantly improving treatment outcomes for infections in hard-to-reach areas such as nails, ears, and oral cavities. Nano-capsule-based formulations enhance drug delivery, bioavailability, and controlled release, particularly in conditions such as onychomycosis and diabetic foot ulcers. From an environmental standpoint, nanomaterials are equally impactful. Their ability to adsorb, degrade, or transform pollutants makes them critical in soil remediation. Various synthesis techniques such as top-down (e.g., mechanical milling, laser ablation) and bottom-up (e.g., sol-gel, green biosynthesis using plant extracts) are continually refined to improve efficiency, scalability, and environmental safety. This paper underscores the interdisciplinary relevance of nanomaterials and their applications in health sciences and environmental sciences.